The psychoanalytical journal, writing and evaluation of psychoanalytical papers. (2nd April 2016) - Sjödin, Christer
Abstract: "What is in the mind of the author?" "What is in the mind of the reviewer?" "What is in the mind of the reader?" "What is in mind of the teacher?" "What is in the in the mind of the publisher?" These themes were discussed in a panel: "The psychoanalytical journal, writing and evaluation of psychoanalytical papers, " at the XVIII International Forum of the IFPS, held in Kaunas (Lithuania), in September 2014.